Mechanical Analysis on the Transmission Mechanism of 35 Type Gear Long Ring Rack Pumping Units - Peng Zhenhua; Ding Wen; Ren Xianghai; Gao Leilei; Xu Haiying; Wang Zenan; Wang Hanxiang; Zhang Xin (Jixie chuandong)
Taking a new type of 35 pumping unit suitable for deep well mining as the research object, the mechanical analysis of its gear long ring rack transmission mechanism is carried out to solve the problems of short operation cycle and high energy consumption in deep well mining with electric submersible pump. The mechanical model of the transmission mechanism is established and the force variation law of the gear long ring rack is obtained in the process of reversing. Based on the dynamic simulation of the pumping unit operation process using Adams, the dynamic characteristics of the transmission mechanism and rollers are studied and the influence of dynamic on the pumping unit operation state is analyzed. The results show that the force of the transmission mechanism changes with the gear position in the process of commutation. During the up and down stroke, the size and direction of the force on the long ring rack are different. The rack box is overturned around its own x, y and z axes. The pneumatic counterweight of 7 t is the best counterweight of the pumping unit. The research results can provide a theoretical reference for the further improvement and optimization of the pumping unit parts.